Criminalization of Freedom of Assembly in Indonesia - Mispansyah Mispansyah; Nurunnisa Nurunnisa; Tiya Erniyati (Islamic Research, 2023)
This study aims to analyze Law No. 16 of 2017 concerning Social Organizations in accordance with the Rule of Law Principles and find forms of formulative policies to revoke the status of Legal Entities of Community Organizations Association in the future (Ius Constituendum). This research is a normative legal research using 3 types of approaches: Statute Approach, Conceptual Approach, Case Approach related to the laws and regulations on Social Organizations. The results of this study indicate that Law No. 16 of 2017, which criminalizes freedom of assembly is not following the principles of the state law and even against the principles of the state law, and has the potential to lead to repressive actions to create a dictatorial ruler. Future formulative policies in realizing freedom of association and assembly, the Law on Community Organizations must continue to guarantee a fair judicial process (due process of law) as regulated in Law Number 17 of 2013 concerning Social Organizations, and the sanctions given are sufficient sanctions. Administratively by suspending or revoking the status of a legal entity association or suspending or dissolving community organizations.